Blockchain enabled privacy provisioning scheme for location based services in VANETs - Iqra Ilyas; M. Usman Ashraf; Sami S. Albouq; Khlood Shinan; Hanan E. Alhazmi; Fatmah Alanazi; Saqib Ali (PLoS ONE, 2025)
In recent years, vehicular ad hoc networks (VANETs) have emerged as a crucial component of intelligent traffic systems, offering enhanced road safety through autonomous, distributed, and dynamically structured communication. However, ensuring secure and privacy-preserving message broadcasting in VANETs remains a significant challenge due to their open-access nature. Existing solutions have addressed various security and privacy concerns, yet critical issues such as resistance to traffic analysis, unlinkability of messages, computational efficiency, and location privacy remain underexplored. To bridge these gaps, we propose a blockchain-based privacy-preserving scheme that strengthens VANET security while addressing unobservability, unlinkability, and efficiency in authentication. Our approach leverages a cache-based anonymizer server positioned between the On-Board Unit (OBU) and the Roadside Unit (RSU), which enhances privacy by masking communication patterns and improves efficiency by reducing authentication overhead. Performance evaluations demonstrate that our scheme significantly reduces computational costs, achieving 95.17% to 97.00% reduction in V2V and 97.81% to 98.90% reduction in V2RSU communication time compared to referenced schemes. Additionally, our approach reduces communication cost by 67.94% to 81.67% for V2V and 72.40% to 88.00% for V2RSU, while the location leakage probability is minimized to 0.05% which is significantly lower than centralized architectures. Furthermore, our scheme ensures strong privacy protection, attaining a maximum entropy level of 5 which is 95.8% higher than existing schemes. These results confirm that our framework minimizes computational overhead, optimizes communication efficiency, and enhances privacy protection, making it a robust and scalable solution for VANET systems.